Magnetotransport Study of van der Waals CrPS4/ (Pt,Pd) Heterostructures: Spin-Flop Transition and Room-Temperature Anomalous Hall Effect - Wu, Rui; Ross, Andrew; Ding, Shilei; Peng, Yuxuan; He, Fangge; Ren, Yi; Lebrun, Romain; Wu, Yong; Wang, Zhen; Yang, Jinbo; Brataas, Arne; Klaeui, Mathias (Physical Review Applied, 2022)
We study magnetotransport in heterostructures composed of the van der Waals antiferromagnet CrPS4 and the heavy metals Pt and Pd. In both types of devices, the transverse resistance (Rxy) signal reveals the spin-flop transition of CrPS4 and a strong anomalous Hall effect at temperatures up to 300 K. While CrPS4/Pt devices allow for easy detection of the spin-flop transition, CrPS4/Pd devices show a more substantial enhancement in anomalous Hall effect at temperatures above 70 K and exhibit a topological Hall effect signal, possibly related to chiral spin structures at the interface. The longitudinal magnetoresistance (Rxx) results from a combination of spin-Hall magnetoresistance and the negative magnetoresistance that can be explained by a field-induced change of the electronic band structure of CrPS4.
CRIS-Team Scopus Importer:2023-03-27